Sustainable development of public administration: suggestions for improvement of the functional analysis in government bodies (Journal of Economic Research & Business Administration, 2016)
This article deals with the functional analysis as a tool for public ad-ministration reform in Kazakhstan. Functional analysis helps to identify du-plication of functions, lack of coordination between public authorities and the possibility of functions transfer that could be better performed by the private sector or civil society.Unfortunately, structural reorganizations following the functional anal-ysis were insufficient to promote a radical reform, as it was not concerned with the clarification of the role of state in the transition period and the determination of state functions. Therefore, many of the “old” function, declaredin the statutes of ministries and departments dopersist. In the meanwhile, “new” functions emerge. As a result, regular downsizing of central administrative offices rather lead to a weakening of public admin-istration’s internal potential than enhance the efficiency.
Keywords: government bodies; public administration; functional analysis; principles; functions.